(untitled) (Applied Biological Research, 2017)
The genomic information available for finger millet is very scarce though the plant is a rich source of highly digestible proteins and dietary fibre with good amounts of soluble and insoluble fractions. In present study, 64 maize and finger millet genomic SSRs were used for cross transferability, identification of polymorphic markers and genetic diversity of finger millet, both cultivated and wild species. Out of 64 SSRs, only 43 (67%) were amplified across the finger millet genotypes. The PIC values of all the polymorphic loci across the 23 finger millet genotypes varied from 0.04 to 0.47 (average value 0.17). Based on the parameters of PIC values ≥ 0.26, gene diversity ≥0.43, inbreeding coefficient ≥ 0.60, the SSR loci UGEP33, UMC1858, UMC1805, and UMC2163 were found highly polymorphic. Comparison of SSR polymorphism in finger millet genotypes revealed that microsatellites of maize were more polymorphic and were able to identify more diversity in finger millet genotypes than the finger millet SSRs. Good correlations were found between genetic diversity analysis in differentiation of finger millet genotypes using finger millet and maize microsatellite markers. Dendrogram generated through UPGMA analysis grouped all the 23 genotypes clustered them into two major groups A and B with maximum similarity found between genotype pairs T552, T622 and T507, T74. The genotype pairs T671 and T760; T187 and T 631, T824 showed lowest similarity in finger millet which could be selected for hybrid plant production. The present study enriched the finger millet genomics by identifying suitable polymorphic markers of maize and finger millet, which can be used for diversity analysis, cultivar identification and QTL mapping studies.